Report on centre-tap single-phase inverter / Azman Zainal - Zainal, Azman (1991)
A study of a single-phase centre-tapped inverter using two power transistors has been made. In this work, the biasing circuit is derived from a 50Hz supply. Various different waveforms were photographed and analysed.